Design parameters for seismically retrofitted masonry-to-timber connections: injection anchors - Moreira, Susana (2016)
Proper structural connections play an important role in ensuring seismic loads distribution and developing global damage mechanisms of structures. In historical unreinforced masonry buildings, effective connections between masonry walls and timber floors or walls through the use of anchors can prevent the occurrence of out-of-plane mechanisms and promote box-like behavior. Particularly for historic structures, injection anchors can comply with requirements as decreased architectural impact and minimum intervention. Therefore, this paper aims at developing structural design parameters and recommendations that allow the design of connections retrofitted with injection anchors, found in historical unreinforced masonry buildings, built during the 19th century, in Portugal. Existing strength prediction formulae based on behavior models, and idealized force-displacement curves were developed to better fit the results obtained from a series of quasi-static monotonic and cyclic pullout tests carried out on pairs of injection anchors. Behavior models were able to approximate the experimental results, if adapted to the specificities of historical masonry. Further validation is needed, particularly for the combined cone-bond model. From the idealized curves, displacement acceptance criteria, expected forces, and behavior factors were proposed, according to the performance-based approaches recommended by EC8-Part 3 and ASCE/SEI 41-13. Finally, retrofit design recommendations were addressed.